Assessing Mental Health Awareness and Self-Care Practices to Prevent Suicidal Thoughts among Students at Janata Multiple Campus (JMC) - Aryal, Sayeja (Journal of Janta Multiple Campus, 2025)
This study explores mental health awareness, self-care practices, coping strategies, and suicide prevention among students at Janta Multiple Campus (JMC). It focuses on their understanding, attitudes, and behaviors related to mental well-being. A mixed-methods approach was adopted, combining both quantitative surveys and qualitative tools. Data were gathered from 150 students across the Management, Education, and Humanities departments through structured questionnaires, including both closed- and open-ended questions. Additionally, three focus group discussions (each with 10 students) and in-depth interviews were conducted to capture deeper insights into students’ personal experiences and perceptions. Findings suggest that while most students are aware of mental health issues, stigma remains a significant barrier to seeking professional help. Common stressors include financial challenges, family-related pressures, and academic workload. Although many students attempt self-care through journaling, meditation, or physical activity, these practices tend to be inconsistent. Alarmingly, a notable number of students admitted to having experienced suicidal thoughts, yet they often turn to informal networks such as friends or family rather than professional counseling. These insights underscore the urgent need for campus-based mental health programs that not only raise awareness but also reduce stigma and ensure accessible, student-friendly support systems.